Photocatalytic Hydrogen Evolution by a Synthetic [FeFe] Hydrogenase Mimic Encapsulated in a Porphyrin Cage - Nurttila, Sandra S. (Chemistry, 2018)
The design of a biomimetic and fully base metal photocatalytic system for photocatalytic proton reduction in a homogeneous medium is described. A synthetic pyridylphosphole‐appended [FeFe] hydrogenase mimic was encapsulated inside a supramolecular zinc porphyrin‐based metal–organic cage structure Fe(4)(Zn‐L)(6). The binding is driven by the selective pyridine–zinc porphyrin interaction and results in the catalyst being bound strongly inside the hydrophobic cavity of the cage. Excitation of the capsule‐forming porphyrin ligands with visible light while probing the IR spectrum confirmed that electron transfer takes place from the excited porphyrin cage to the catalyst residing inside the capsule. Light‐driven proton reduction was achieved by irradiation of an acidic solution of the caged catalyst with visible light.